The Politeness Strategy Employed by Teachers in EFL Classrooms and Its Impact on the Learning Process - Mujiati; Trisnian Ifianti (Universitas Insan Budi Utomo, 2024)
The objective of this study was to clarify the specific methods of politeness used during interactions between teachers and students in an English as a Foreign Language (EFL) classroom, and to analyze the influence of these strategies on the educational process. The author chose to gather data from the tenth-grade students of SMA Negeri 1 Ngantang throughout the academic year 2023/2024. The study encompassed the entire group of individuals involved in an English as a Foreign Language (EFL) classroom, comprising both the teacher and the students. The study involved 20 participants in total. Data was gathered in a natural environment, with the researcher observing the teaching and learning activities without implementing any modifications or interventions.The data was analyzed using Miles & Huberman's (1994) interactive cycle model of qualitative data analysis, which involved three simultaneous processes: data reduction, data presentation, and drawing or verifying conclusions. It identified four unique politeness strategies: bald on record, positive politeness, negative politeness, and off record. According to the findings, the researcher concluded that the teacher exhibited positive politeness during the instructional activities. Furthermore, the teacher utilized polite language and their demeanor was marked by attentiveness, delight, and friendliness. The majority of students in the class displayed exemplary etiquette by showing deference to their teacher throughout the instructional and educational endeavors.